Molecular characterization, carbohydrate metabolism and tolerance to abiotic stress of Eremothecium coryli endophytic isolates from fruits of Momordica indica - Dos Reis, Jefferson Brendon Almeida; Rodrigues, Mayara Oliveira Sousa; Furtado, Leila Lourenço; de Sousa Queiroz Júnior, Clemildo; do Vale, Helson Mario Martins (Folia microbiologica, 2025)
Yeasts are unicellular fungi that occur in a wide range of ecological niches, where they perform numerous functions. Furthermore, these microorganisms are used in industrial processes, food production, and bioremediation. Understanding the physiological and adaptive characteristics of yeasts is of great importance from ecological, biotechnological, and industrial perspectives. In this context, we evaluated the abilities to assimilate and ferment different carbon sources, to produce extracellular hydrolytic enzymes, and to tolerate salt stress, heavy metal stress, and UV-C radiation of two isolates of Eremothecium coryli, isolated from Momordica indica fruits. The two isolates were molecularly identified based on sequencing of the 18S-ITS1-5.8S-ITS2 region. Our isolates were able to assimilate nine carbon sources (dextrose, galactose, mannose, cellobiose, lactose, maltose, sucrose, melezitose, and pectin) and ferment three (glucose, maltose, and sucrose). The highest values of cellular dry weight were observed in the sugars maltose, sucrose, and melezitose. We observed the presence of hyphae and pseudohyphae in all assimilated carbon sources. The two isolates were also capable of producing amylase, catalase, pectinase, and proteases, with the highest values of enzymatic activity found in amylase. Furthermore, the two isolates were able to grow in media supplemented with copper, iron, manganese, nickel, and zinc and to tolerate saline stress in media supplemented with 5% NaCl. However, we observed a decrease in CFU at higher concentrations of these metals and NaCl. We also observed morphological changes in the presence of metals, which include changes in cell shape and cellular dimorphisms. The isolates were sensitive to UV-C radiation in the shortest exposure time (1 min). Our findings reinforce the importance of endophytic yeasts for biotechnological and industrial applications and also help to understand how these microorganisms respond to environmental variations caused by human activities.
Keywords: Phylogeny; ovoce; Metals, Heavy; Endophytes; Saccharomycetales; fermentace; ultrafialové záření; fyziologický stres; Endophytic fungi; endofyty; Carbohydrate Metabolism; Fermentation; Dimorphism; Ultraviolet Rays; metabolismus sacharidů; Malt; fylogeneze; Fruit; těžké kovy; Life-history strategies; Stress, Physiological; Life-history traits